Na.a M. Shah and M. Anwar. Basic Needs, Women and Development. A Survey of Squatters in Lahore, Pakistan. Ottawa: International Development Research Center and honolulu: East-West Center. 1986. 163pp. (The Pakistan Development Review, 1988)
This book is essentially the report of a survey carried out to investigate the basic needs of Katchi Abadi populations in Lahore city. Given that about 25-30 percent of Pakistan 's population is estimated 10 be Jiving in such squatter settlements and with the ever increasing migration to urban areas, this proportion is only likely to rise. Thus, this research is most invaluable for urban planners and demographers in particular, and social scientists in general. Whereas previous studies have concentrated on examining levels of urban and rural poverty by using macro-level data, this study is based on an originally designed empirical investigation of low income areas. The major aim of the research seems to be the question of whether or not the fruits of development are in fact "trickling down" to the poorest classes in the urban areas. By implication, the answer if in the positive, means that recent development plans in Pakistan have been successful, if negative , the answer draws attention to the failure of development planning to carry out redistributive justice.